Role of inter-organizational knowledge acquisition in bringing green innovation in manufacturing SMEs: An investigation of green organizational culture and absorptive capacity - Sakhawat-ur-rehman; Muhammad Yasir; Abdul Majid; Samar Hayat Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
This study focus upon the significant issue that how inter-organizational knowledge acquisition (IOKA) enhances the green innovation (GI) through mediating role green organizational culture (GOC) and moderating role of absorptive capacity (AC). Contextualizing manufacturing SMEs, this study empirically tested model of green innovation to entail comprehensive mechanism to analyze its imperative determinants. Survey method was employed, and data was gathered from CEOs, owners and managerial level employees of manufacturing SMEs. Hierarchical regression was applied to verify the proposed hypotheses. Study finding confirmed the positive association between interorganizational knowledge acquisition, green organizational culture, and green innovation. Findings also approved that GOC mediates the association of IOKA, and GI. Additionally, AC strengthens the relationship between IOKA, and GI. Study contributes to theory through entailing insights relating influence of IOKA, GOC and AC on GI of enterprise along with mediating role of GOC and moderating role of AC in relationship of IOKA and GI. This study is useful for SMEs' management to devise strategies of adopting green practices in current environment
Keywords: 330; Inter-organizational knowledge acquisition; green organizational culture; absorptive capacity; green innovation; manufacturing SMEs; ISO9001; ISO14001